An Analysis of Figurative Language in Autumn!S Album Golden Child, Chapter 3 - Kamarizki, Reynaldi; Wuryandari, Dyah Ambar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Figurative language refers to the use of expressive linguistic tools that transcend literal interpretation to convey deeper meanings and evoke vivid imagery. In light of this definition, this researchs objective is to find out the types of figurative language and to find out the most dominant type of figurative language in Autumn!'s album